Sustainable Business Models - Adam Jabłoński (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The dynamically changing world economy, in an era of intensive development and globalization, creates new needs in both the theoretical models of management and in the practical discussion related to the perception of business. Because of new economic phenomena related to the crisis, there is a need for the design and operationalization of innovative business models for companies. Due to the fact that in times of crisis, the principles of strategic balance are particularly important; these business models can be sustainable business models. Moreover, it is essential to skillfully use different methods and concepts of management to ensure the continuity of business. It seems that sustainable business models, in their essence, can support companies' effectiveness and contribute to their stable, sustainable functioning in the difficult, ever-changing market. This Special Issue aims to discuss the key mechanisms concerning the design and operationalization of sustainable business models, from a strategic perspective. We invite you to contribute to this Issue by submitting comprehensive reviews, case studies, or research articles. Papers selected for this Special Issue are subject to a rigorous peer review procedure, with the aim of rapid and wide dissemination of research results, developments, and applications.